Segregate Garbage and Takakura Bag as One of the Efforts to Minimize Waste in Islamic Boarding Schools - Khuliyah Candraning Diyanah; Nuzulul Kusuma Putri; Aditya Sukma Pawitra; J. Mukono; Soedjajadi Keman; Ririh Yudhastuti; Lilis Sulistyorini; R. Azizah; Sudarmaji Sudarmaji; Retno Adriyani; Corie Indria Prasasti; Muhammad Farid Dimjati Lusno; Kusuma Scorpia Lestari; Zida Husnina; Novi Dian Arfiani; Desi Listianingsih; Eny Rohmawati (Faculty of Public Health, University of Jember in collaboration with PERSAKMI, 2023)
Waste problems in Islamic boarding school is commonly caused by the low awareness of students and others individuals in practicing new paradigm of 3R waste management method (reduce, reuse, recycle). Target partner in empowering the community is Al Amin Boarding School Tunggul Paciran Lamongan. This empowerment program is built based on Dignan theory, starting with community analysis, targeted assessment, program plan development, implementation and evaluation. The Activities in September – October 2022. Our health education was successfully increased the students’ knowledge about waste management up to 86,6%, the students also were able to sort their waste, and did organic composting using Takakura bag.